Diurnal cycle of fossil and nonfossil carbon using radiocarbon analyses during CalNex. Issue 11 (3rd June 2014) - Zotter, Peter; El‐Haddad, Imad; Zhang, Yanlin; Hayes, Patrick L.; Zhang, Xiaolu; Lin, Ying‐Hsuan; Wacker, Lukas; Schnelle‐Kreis, Jürgen; Abbaszade, Gülcin; Zimmermann, Ralf; Surratt, Jason D.; Weber, Rodney; et al.
Abstract Radiocarbon (14C) analysis is a unique tool to distinguish fossil/nonfossil sources of carbonaceous aerosols. We present 14C measurements of organic carbon (OC) and total carbon (TC) on highly time resolved filters (3–4 h, typically 12 h or longer have been reported) from 7 days collected during California Research at the Nexus of Air Quality and Climate Change (CalNex) 2010 in Pasadena. Average nonfossil contributions of 58% ± 15% and 51% ± 15% were found for OC and TC, respectively. Results indicate that nonfossil carbon is a major constituent of the background aerosol, evidenced by its nearly constant concentration (2–3 μgC m−3). Cooking is estimated to contribute at least 25% to nonfossil OC, underlining the importance of urban nonfossil OC sources. In contrast, fossil OC concentrations have prominent and consistent diurnal profiles, with significant afternoon enhancements (~3 μgC m−3), following the arrival of the western Los Angeles (LA) basin plume with the sea breeze. A corresponding increase in semivolatile oxygenated OC and organic vehicular emission markers and their photochemical reaction products occurs. This suggests that the increasing OC is mostly from fresh anthropogenic secondary OC (SOC) from mainly fossil precursors formed in the western LA basin plume. We note that in several European cities where the diesel passenger car fraction is higher, SOC is 20% less fossil, despite 2–3 times higher elemental carbon concentrations, suggesting that SOC formation from gasoline emissions most likely dominates over diesel in the LA basin. This would have significant implications for our understanding of the on‐road vehicle contribution to ambient aerosols and merits further study.